EFEKTIVITAS AKUN INSTAGRAM @VISIT_SINGAPORE TERHADAP PEMENUHAN KEBUTUHAN iINFORMASI WISATA FOLLOWERS - Susanty, Susy; Abidin, Sholihul (SCIENTIA JOURNAL, 2021)
Social media is used to disseminate a variety of information that supports meeting the public's information needs. The simple use of Instagram allows users to reach their needs or purpose of surfing. Instagram account @Visit_Singapore is one of those accounts that uses Instagram social media to provide information. Instagram account @Visit_Singapore spreads information about Singapore tourism. In this study, the researchers took the population of followers on the @Visit_Singapore Instagram account. A non-probability technique was used to select 348 individuals as the sample. The purpose of this study is to know the effectiveness of the @Visit_Singapore Instagram account in meeting the follower tourist information needs. This type of study is a quantitative study and one that determines some of the hypotheses to be tested. The survey method is a method of distributing link questionnaires to followers of @Visit_Singapore Instagram account through direct message function. Test results with t meaning less than 0.000 (0.000 <0.05) mean that the variable effect of the Instagram account @Visit_Singapore is effective in meeting the follower tourist information needs.